PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID UNTUK SEKOLAH DASAR KELAS V - Yuni Purnama; Muhammad Asrori; Dede Suratman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This Article to describe the level of feasibility, learning materials, and utilization of android-based learning videos developed in Elementary School class V. The research model uses Four D (4D) from Thiagarajan which includes the Define, Design, Develop and Dessiminat stages. which has been adapted, namely by the following stages of development research (1) product discovery, (2) product manufacturing, (3) product development and (4) product dissemination. Based on the exposure of research results and discussions obtained in conclusions, namely (1) the learning video developed was concluded to be in the category of very feasible with a value of 90.63; (2) The learning material developed in the learning video includes a Indonesian content, namely about the main idea of a paragraph, the IPA content regarding human and animal organs and the PKn content regarding the character of how to be grateful for the favor bestowed by Allah SWT. (3) Developed learning video products are used in independent learning online and in the classroom through limited face-to-face learning.